Thank you, a good research antioxidant, antimicrobial and toxicity studies of the different fractions of fruits of Terminalia belerica Roxb - Alam, Md. Badrul; Zahan, Ronok; Hasan, Mahedi; Maruf, M; Khan, Md. Maruf; S Rahman, Nargis; Chowdhury, M; Haque, Ekramul (© IDOSI Publications, 2011., 2016)
This article was published in Global Journal of Pharmacology [© IDOSI Publications, 2011] and the definite version is available at: http://idosi.org/gjp/5(1)11/3.pdf